2016
DOI: 10.1088/0029-5515/57/2/022017
|View full text |Cite
|
Sign up to set email alerts
|

The global build-up to intrinsic ELM bursts and comparison with pellet triggered ELMs seen in JET

Abstract: We focus on JET plasmas in which ELMs are triggered by pellets in the presence of ELMs which occur naturally. We perform direct time domain analysis of signals from fast radial field coils and toroidal full flux azimuthal loops. These toroidally integrating signals provide simultaneous high time resolution measurements of global plasma dynamics and its coupling to the control system. We examine the time dynamics of these signals in plasmas where pellet injection is used to trigger ELMs in the presence of natur… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 37 publications
1
6
0
Order By: Relevance
“…29 In these JET plasmas, we found that the phase of toroidal full flux loop signals became aligned around a single value just before the onset of each natural ELM. [29][30][31][32] In particular, 30 we found a class of prompt natural ELMs which are at distinct short inter-ELM time intervals that occur at a specific phase of the plasma's own response to the previous ELM. For these ELMs, the initial ELM and its successor form a linked pair, in that the second ELM arises near the end of the first.…”
Section: Discussionmentioning
confidence: 87%
See 3 more Smart Citations
“…29 In these JET plasmas, we found that the phase of toroidal full flux loop signals became aligned around a single value just before the onset of each natural ELM. [29][30][31][32] In particular, 30 we found a class of prompt natural ELMs which are at distinct short inter-ELM time intervals that occur at a specific phase of the plasma's own response to the previous ELM. For these ELMs, the initial ELM and its successor form a linked pair, in that the second ELM arises near the end of the first.…”
Section: Discussionmentioning
confidence: 87%
“…The vertical control coil current phase may provide a parameter that orders ELM cycle dynamics even if the ELM frequency is drifting. On JET, we found a class of prompt [29][30][31][32] natural ELMs that occur at a specific phase of the plasmas own response to the previous ELM. We would thus expect under some plasma conditions a global dynamics where all the ELMs are "prompt" with each ELM directly following the previous one.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…This process modifies the current in the field coils, generating inductive magnetic fields that react back on the plasma. The question is then whether in the absence of any external driving, the non-linearly coupled global plasma and control system dynamics plays a role in the physics of naturally occurring ELMs [27][28][29][30][31]33].…”
Section: Introductionmentioning
confidence: 99%